Sub-Classification of AO/OTA-2018 Pertrochanteric Fractures Is Associated With Clinical Outcomes After Fixation of Intramedullary Nails - Hui Song MD (SAGE Publishing, 2021)
Background The new edited AO/OTA-2018 classification of pertrochanteric fractures was revised and no longer based on the status of lesser trochanter. This paper aimed to explore the clinical and technical outcomes among the subgroups (31A1 and 31A2) of the new classification treated with cephalomedullary nails. Methods A retrospective research of 154 patients diagnosed with pertrochanteric fractures (AO/OTA-2018 31A1.2/3 and 31A2.1/2/3) treated with intramedullary nails was conducted. The baseline data and outcomes were compared among the subgroups. The outcomes included tip-apex distance (TAD), Cal-TAD, Parker ratio, neck shaft angle (NSA), blood loss, varus displacement, and over lateral sliding rate of the blade. Results There were 154 cases involving 48 males and 106 females. The average age was higher in the sub-classifications of A2.2 and A2.3 than A1.2. Furthermore, the subgroups of A2.2 and A2.3 presented inferior outcomes with regard to blood loss and reduction quality score than A1.2 and A1.3. The subgroup of A2.3 was further poor with respect to calcar fracture gapping in the anteroposterior view and excessive lateral migration occurrence rate than A1.2. Conclusions Complex pertrochanteric fractures indicated inferior outcomes compared to simple sub-classifications, which might lead by the incompetent of lateral wall and instability of the fracture. The newly proposed AO/OTA-2018 classification was conductive to forecast the prognosis.